Cereal consumption and marketing responses by rural smallholders under rising cereal prices - Mottaleb, Khondoker Abdul; Rahut, Dil Bahadur (Emerald Publishing Limited, 2018)
International commodity prices have escalated to an unprecedented level since 2008. Although commodity prices have declined recently, prices are still high compared to the pre-2008 levels. Combining this market phenomenon with Bangladesh Government’s Household Income and Expenditure Survey (HIES) data sets HIES 2005 and HIES 2010, and applying the seemingly unrelated regression (SUR) estimation process, the purpose of this paper is to examine paddy rice marketing, and the cereal and non-cereal food expenditure behavior of rural smallholders in Bangladesh under rising commodity prices.This study uses information collected by the Government of Bangladesh and applies two-step Heckman-type selection model estimation procedure, first to estimate total rice production by the rice production self-sufficiency status of the household. Second, the study estimates the paddy marketing behavior by the households by their rice self-sufficiency status under rising commodity price regime applying SUR estimation process combing with Heckman’s selection model estimation procedure.Empirical findings demonstrate that there was no positive assertion between higher paddy rice prices and paddy rice marketing by the rural smallholders. Rather, under the rising commodity price regime, smallholders significantly reduced consumption expenditure on high food value-enriched non-cereal food items to adjust to the market shocks.This is a Bangladesh-based case study. Individual country-level case studies should be conducted in order to generalize the findings of the present study.The present study warns that the market volatility may discourage farm households to market their cereals more due to uncertain future. To the authors’ knowledge, this is the first attempt to explore the cereal marketing behavior of the farm households in Bangladesh under commodity price hikes by the rice production self-sufficiency status of the farm households.